The effects of a tax allowance for growth and investment: Empirical evidence from a firm-level analysis - Matthias Petutschnig; Silke Rünger (Arbeitskreis Quantitative Steuerlehre (arqus), 2017)
We contribute to the empirical literature on the debt bias of corporate income taxation through a firm-level evaluation of the European Commission's recent proposal of an Allowance for Growth and Investment (AGI). We use the introduction, the application and the repeal of a similar allowance in Austria during the early 2000s to evaluate the effects of the AGI on corporate equity and profit distribution. Our analysis provides evidence that such an allowance could increase corporate equity ratios by 5.5 percentage points and reduce profit distributions by 7.6 percentage points. These effects are stronger than those the previous literature for traditional Allowance for Corporate Equity (ACE) tax systems has identified. Additionally, we contribute to the recently expanding literature on the influence of ownership on tax planning as we find significant differences in the utilization of the AGI depending on individual specifics of the majority shareholder as well as depending on the number of shareholders of the respective firms
Keywords: G32; H24; H25; K34; 330; taxes; retained earnings; tax allowance; notional interest deduction; AGI; ACE